RESPONS LOKAL TERHADAP REVOLUSI INDONESIA DI SUNDA KECIL, 1945 – 1950 - A.A Bagus Wirawan (Humaniora, 2008)
Many studies about national revolution or freedom war more likely show their view based on the “national” perspective. But recently, It seems to be necessary to see from the local perspective. Only based on the local perspective which elevates the response of local dynamic, the understanding of the National Revolution will be better and having much more complete illustration. The local dynamic can be a reflection of the main territory command, which has autonomous characteristic, and the local events represent the authentic reflection of internal dynamic, although the fluctuation is influenced by outsider. In other words, the events of local dynamics such as the response of the local people to revolution taking place in Sunda Kecil are very relevant to explain the National Revolution which was indicated by the beginning process of forming nation identity toward the modern Republic of Indonesia.